Effect of Irrigation and Potash Levels on Keeping Quality of Potato - Adhikari, Ram Chandra; Rana, Mahesh Kumar (Journal of Nepal Agricultural Research Council, 2020)
Irrigation and fertilizer are the most dominating factors, in deciding the keeping quality of potato. It is, therefore, essential to formulate the efficient, reliable and economically viable irrigation management strategy with the use of potassium nutrient in order to produce better keeping quality. The investigation comprising four levels of irrigation (25, 30, 35 and 40 mm CPE (Cumulative pan evaporation) and four levels of potash (0, 100, 125 and 150 kg/ha) was carried out at Research Farm of the Department of Vegetable Science, CCS Haryana Agricultural University, (Haryana) Hisar, India during two years to find out the optimum level of irrigation and potash for obtaining higher yield of potatoes with better keeping quality at ambient room temperature. The potato variety used for the investigation was Kufri Bahar. The treatments were laid out in a split plot design with three replications. The increasing levels of irrigation and potash showed significant improvement in keeping quality parameters of potato. Likewise, the values for physiological loss in weight and decay loss of potato tubers (%) at 15, 30, 45 and 60 days after harvest were the lowest with irrigation level 40 mm CPE and application of potash @ 150 kg/ha. The two years results suggest that the irrigation level 40 mm CPE along with potash @ 150 kg/ha has shown the best treatment combination for the storage of potato at ambient room temperature under semiarid conditions of Hisar (Haryana).